Manajemen Preoperatif Kehamilan Ektopik Terganggu dengan Syok Hipovolemia - Budianti, Nugrahaeni; Rahardjo, Sri; Uyun, Yusmein (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2017)
Had been reported a case of preoperative management for a woman 36 years old, G1P0A0, pregnant 11 weeks with ruptured ectopic pregnancy and run into hypovolemia shock. We assessed physic status patient as ASA (American Society of Anesthesia) 4E (emergency) with hypovolemia shock et causa internal bleeding and patient had been done relaparotomy. Patient had been refered from RSUD Wonosari and when she came to RSUP Sardjito, she feel pain and pale suspicious hypovolemia shock with internal bleeding then had been done laparatomy emergency surgery, dextra salphingectomy et causa ruptured ectopic pregnancy in IGD operation room for 2 hours and then she was observated in resusitation room for 6 hours and then she was transported to PACU. When in PACU, her condition compos mentis, she feel pain and the hemodynamic is blood pressure 90/ 60 mmHg, pulse 165 times/ minutes, respiration rate 32 times/ minutes on NRM 8 liters/ minutes, spO2 99 – 100 %, temperature 36,8 °C and VAS 3 – 4. In abdominal assessment, we found decreased of peristaltic, distended (+), tenderness (+), wound dressing blood seeped (-) and capilarry refill over 2 second and also radialis artery was not detected. We did evaluation to know internal bleeding, we did positive challange test with kristaloid 20 cc/ kg BB in 15 minutes and then in USG, we found free liquid intraabdomen and we planned emergency laparatomy in IGD operation room. Anesthetic technique that we used was general anesthesia. After surgery, patient was transported to ICU in sedation condition and was intubated.